Diskursus Prinsip Negara Hukum Demokrasi atas Permasalahan Konstitusionalitas Undang-Undang Nomor 3 Tahun 2022 tentang Ibu Kota Negara - Ahmad Habib Al Fikry (CV Rewang Rencang, 2022)
In a state of law, there are principles that are always firmly held in the administration of the state. This principle is a tool to achieve state goals as stated in the constitution. This paper aims to explain the discourse on the principle of a democratic law state on the issue of the constitutionality of Law Number 3 of 2022 concerning the National Capital City (IKN). The results show that there are formal and material problems in the formation of a quo law. The discourse on the principle of a democratic legal state answers this problem, namely by testing the IKN Law to the Constitutional Court, reformulating the National Capital in the IKN Law into a province, the need for a Regional People's Representative Council, and the existence of a mechanism for selecting the head of the authority.